2009
DOI: 10.1590/s0103-50532009000300004
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective transport of D,L-phenylalanine and D,L-phenylglycine through a bulk liquid membrane containing cinchona alkaloid derivatives as chiral selectors

Abstract: Diversos derivados de Cinchona foram testados como carregadores quirais móveis, para o transporte enantiosseletivo de D,L-fenilglicina e D,L-fenilalanina, através de uma membrana líquida orgânica volumosa (MLV). Os efeitos de vários parâmetros, como natureza do carregador, concentrações do solvente na membrana, do tampão, do soluto e do carregador, no enriquecimento quiral da MLV, foram avaliados. Somente a D,L-fenilglicina foi sujeita, em certo grau, ao transporte enantiosseletivo; a razão máxima de enantioss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
(17 reference statements)
1
9
1
Order By: Relevance
“…51 Cinchona alkaloid was also used as a transporter for optical resolution. 52 On the basis of these studies, AAMC was chosen as a transporter for enantioselective transport, and the membrane performance was investigated using a racemic mixture of Phegly as a model racemate.…”
Section: Application Of Pplm For Chiral Separationmentioning
confidence: 99%
“…51 Cinchona alkaloid was also used as a transporter for optical resolution. 52 On the basis of these studies, AAMC was chosen as a transporter for enantioselective transport, and the membrane performance was investigated using a racemic mixture of Phegly as a model racemate.…”
Section: Application Of Pplm For Chiral Separationmentioning
confidence: 99%
“…It has been reported that the ion pairing between positively-charged tertiary amine moiety in the quinuclidine ring of CCND and negatively-charged carboxylate group in the amino acids and the π-π interaction between the quinoline ring of CCND and the phenyl ring of DL-Phe plays a crucial role in the chiral selectivity of the cinchona alkaloids-based chiral column. 26,27 In the present condition, the best ion pairing and the π-π interaction would be attained at pH 5.0.…”
Section: Application To the Ot-cec Chiral Separation Of Amino Acidsmentioning
confidence: 67%
“…Cinchona alkaloid was also used as a transporter for optical resolution [55]. Based on those studies described above, AAMC was chosen as a transporter for enantioselective transport.…”
Section: Resultsmentioning
confidence: 99%